The specificity and role of microglia in epileptogenesis in mouse models of tuberous sclerosis complex. (5th August 2018) - Zhang, Bo; Zou, Jia; Han, Lirong; Beeler, Brennan; Friedman, Joseph L.; Griffin, Elizabeth; Piao, Yue‐Shan; Rensing, Nicholas R.; Wong, Michael
Summary: Objective: Microglial abnormalities have been reported in pathologic specimens from patients with tuberous sclerosis complex (TSC), a genetic disorder characterized by epilepsy, intellectual disability, and autism. However, the pathogenic role of microglia in epilepsy in TSC is poorly understood, particularly whether microglia defects may be a primary contributor to epileptogenesis or are secondary to seizures or simply epiphenomena. In this study, we tested the hypothesis that Tsc1 gene inactivation in microglia is sufficient to cause epilepsy in mouse models of TSC. Methods: Using a chemokine receptor, Cx3cr1, to target microglia, conventional Tsc1 Cx3cr1‐Cre CKO (conditional knockout) mice and postnatal‐inducible Tsc1 Cx3cr1‐Cre ER CKO mice were generated and assessed for molecular and histopathologic evidence of microglial abnormalities, mechanistic target of rapamycin 1 (mTORC1) pathway activation, and epilepsy. Results: Tsc1 Cx3cr1‐Cre CKO mice exhibited a high efficiency of microglia Tsc1 inactivation, mTORC1 activation, increased microglial size and number, and robust epilepsy, which were rapamycin‐dependent. However, Cre reporter studies demonstrated that constitutive Cx3cr1 expression affected not only microglia, but also a large percentage of cortical neurons, confounding the role of microglia in epileptogenesis in Tsc1 Cx3cr1‐Cre CKO mice. In contrast, postnatal inactivation of Tsc1 utilizing a tamoxifen‐inducible Cx3cr1‐CreER resulted in a more‐selective microglia Tsc1 inactivation with high efficiency, mTORC1 activation, and increased microglial size and number, but no documented epilepsy. Significance: Microglia abnormalities may contribute to epileptogenesis in the context of neuronal involvement in TSC mouse models, but selective Tsc1 gene inactivation in microglia alone may not be sufficient to cause epilepsy, suggesting that microglia have more supportive roles in the pathogenesis of seizures in TSC.